2020
DOI: 10.1016/j.apgeochem.2020.104663
|View full text |Cite
|
Sign up to set email alerts
|

Dawsonite and ankerite formation in the LDX-1 structure, Yinggehai basin, South China sea: An analogy for carbon mineralization in subsurface sandstone aquifers

Abstract: The geochemistry and petrology of the LDX-1 structure of the Yinggehai basin, a natural analog of a sedimentary carbon storage site, was investigated to understand the consequences of the charging of CO2 gas in this system. The rocks in this structure are dominated by subarkose and sublitharenite sandstones. The authigenic minerals formed after CO2 injection are dawsonite, microcrystalline quartz, kaolinite and ankerite.Dawsonite and ankerite are formed just beneath a CO2 bearing anticlinal structure due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The carbonate mineral ankerite ((Mg,Fe,Ca)CO 3 ), however, may be favored in conditions at ambient to moderate temperatures [110,111] . Both dawsonite (NaAl(CO 3 )(OH)) and ankerite have been observed in sedimentary formations at high CO 2 pressures and temperatures >60°C [112,113].…”
Section: Mineral Precipitation Ratesmentioning
confidence: 99%
“…The carbonate mineral ankerite ((Mg,Fe,Ca)CO 3 ), however, may be favored in conditions at ambient to moderate temperatures [110,111] . Both dawsonite (NaAl(CO 3 )(OH)) and ankerite have been observed in sedimentary formations at high CO 2 pressures and temperatures >60°C [112,113].…”
Section: Mineral Precipitation Ratesmentioning
confidence: 99%
“…The selection of the secondary minerals could affect the results of the subsequent simulations; therefore, the most relevant minerals were selected based on their reaction mechanisms and previous studies. Dawsonite, anhydrite, and ankerite were included as secondary minerals and were allowed to precipitate to evaluate the possible mineral inclusion of CO 2 in the deposit [35][36][37]. Anhydrite is an anhydrous calcium sulfate that can reduce the amount of CO 2 trapped in the solid phase and can negatively affect rock permeability [38].…”
Section: Estimation Of Geochemical Equilibriummentioning
confidence: 99%
“…It has also been reported that dawsonite is more stable at low pH values (acidity is equilibrated by buffering); therefore, the range of dawsonite stability is limited given the boundaries of the albite dissolution effect. Moreover, significant care must be taken to preserve the dawsonite and ankerite formation under in-situ conditions by maintaining an increased pressure of the injected CO 2 [37]. These minerals may not provide CO 2 fixation at low partial pressure, unlike calcite.…”
Section: Reactive Transport Modeling Of Injected Comentioning
confidence: 99%
“…These are stable enough to be stored for long time periods. Other carbonate minerals such as siderite (FeCO 3 ), dawsonite (NaAl(CO 3 )(OH) 2 ), and ankerite (Ca(Fe,Mg,Mn)(CO 3 ) 2 ) can act as stores of carbon, but may only be stable in subsurface environments (Hellevang et al, 2005;Snaebjörnsdóttir et al, 2014;Yu et al, 2020). Besides carbonates, other products of mineral carbonation and weathering include silica, iron oxides, and clays.…”
Section: Carbonate Products and Other Secondary Mineralsmentioning
confidence: 99%